Contextualizing Entrepreneurship—Conceptual Challenges and Ways Forward - Welter, Friederike (Entrepreneurship Theory and Practice, 2011)
This paper sets out to explore contexts for entrepreneurship, illustrating how a contextualized view of entrepreneurship contributes to our understanding of the phenomenon. There is growing recognition in entrepreneurship research that economic behavior can be better understood within its historical, temporal, institutional, spatial, and social contexts, as these contexts provide individuals with opportunities and set boundaries for their actions. Context can be an asset and a liability for the nature and extent of entrepreneurship, but entrepreneurship can also impact contexts. The paper argues that context is important for understanding when, how, and why entrepreneurship happens and who becomes involved. Exploring the multiplicity of contexts and their impact on entrepreneurship, it identifies challenges researchers face in contextualizing entrepreneurship theory and offers possible ways forward.